The Threat to DEI Initiatives: How Ontario Teacher Hiring Policies Privilege Whiteness - Abawi, Zuhra; Tuters, Stephanie; Startup, Aurra (Critical Education, 2026)
Given the recent increase in attacks on diversity, equity, and inclusivity (DEI) policies in North America and beyond, we explore the context surrounding recent changes to hiring policies for teachers in Ontario, Canada. The pressures to revoke policies are not new, and have been present in Ontario for many years, resulting in a roller coaster of policy enactments and revocations such as with Regulation 274/12 and PPM 165. The initial enactment of Ontario Regulation 274/12 that was intended to tackle issues of racism and discrimination in hiring practices was widely misunderstood and misconstrued by those who do not support DEI policies causing regulating bodies to publish articles debunking myths surrounding the policy. However, misconception and lack of support remained, which encouraged the Ontario Government to inevitably revoke PPM 165. In this article, we explore the social and political context surrounding the policies and the policy changes to help the reader understand the true purpose and utility of policies such as Regulation 274/12. It is our hope that administrators and hiring committees will find this information helpful as they attempt to hire teachers for their schools. Given the current political climate, this type of exploration is more important than ever.